THE IMPACT OF EARMUFF USE ON HEARING FUNCTION IMPAIRMENT AND FATIGUE: A TIME SERIES STUDY AMONG WEAVING WORKERS IN SURAKARTA, INDONESIA - Haris Setyawan; Nisa Nur Kusuma; Ratih Andhika Akbar Rahma; Tofan Agung Eka Prasetya (Universitas Airlangga, 2026)
Introduction: Hearing loss is identified to impact 466 million people globally, with workplace noise contributing to 16% of adult hearing function impairment. To address the challenges, using personal protective equipment, such as earmuffs, has become a practical solution. Aims: This study aims to analyze impact of using earmuffs on hearing function impairment and fatigue among weaving workers at PT IIPT Surakarta. Methods: The quasi-experimental study used the time series design method, comprising 33 weaving machine operators. Data were collected over 6 working days, namely the first day before the intervention and the following 5 days during the intervention. A questionnaire with tested validity and reliability was used to assess hearing function impairment and fatigue. Results: The results showed that there was a significant variation in the average scores for hearing function impairment and fatigue during the 6 days of earmuff use. Furthermore, the lowest average score was recorded on the first day, while the highest was recorded on the sixth day. Conclusion: This study shows that earmuffs designed to protect workers from the harmful impact of noise increase the average levels of hearing function impairment and fatigue. Consequently, further studies are recommended to evaluate the effectiveness of the sound-absorbing materials used in earmuffs, as different materials can offer varying benefits in absorbing various sources of sound.